Development of low cost agarwood essential oil extraction system for agar tree growers in Bangladesh - Islam, MA; Hussain, MD; Kabir, E; Hasan, MZ (Journal of the Bangladesh Agricultural University, 2014)
This experiment was conducted to bring in a suitable and economic agarwood oil extraction method for Agar tree (Aquilaria agollocha) growers in Bangladesh. Agarwood was collected from Fotikchori upazila of Chittagong district and a prototype of hydro-distillation extraction chamber was developed at the lab of Department of Farm Power and Machinery, Bangladesh Agricultural University, Mymensingh, Bangladesh during January to March 2013. Using the prototype, 7 ml of agarwood oil was extracted from 15 kg matured agarwood. It was found from the calculation that the developed system can bring yearly benefit of Tk. 7,78,389 with benefit-cost ratio as 2.33. This development was, therefore, proven very beneficial for Bangladeshi agar tree growers. DOI: http://dx.doi.org/10.3329/jbau.v12i1.21407 J. Bangladesh Agril. Univ. 12(1): 167-170, June 2014